O protagonismo do Tribunal Superior Eleitoral e o seu impacto na relação de accountability entre Legislativo e Judiciário - Oliveira, Geovane Pedro (Universidade Federal de São Carlos, 2018)
The goal of this paper is to evaluate the implications of electoral justice activism in political-party competition by creating new law in this current republic. That is, although it is not within its competence, the TSE has been carrying out these functions, through new rules that, in turn, have implications both in the system of political representation, and in the relation of horizontal accountability and between the Powers of the Republic. We start from the premise that the model of electoral governance adopted in Brazil favors judicial activism through resolutions issued by the Superior Electoral Court, since such an independent and specialized model excludes political parties from managing the electoral process, making the production of consensus of political party competition is left to the TSE. Resolutions will be analyzed according to their origin, scope and political consequence in order to assess whether the Court has acted as a "legislative power" or have taken decisions of mere interpretive character in the light of the Federal Constitution. The hypothesis is that judicial activism of the Higher Electoral Court has been used as an instrument of horizontal accountability by the Judiciary, that is, control of the electoral and legislative action of the Executive and Legislative Branch, atypically by means of the creation of law in addition to its constitutional competence to regulate electoral matters.
The role of the Higher Electoral Court and its impact on the accountability relationship between the Legislative and Judiciary
Keywords: Justiça eleitoral; Competição política; Judicialização; Sistema político; Electoral justice; Horizontal accountability; Political competition; Judicialization; Political system; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO